OFF AXIS INCLINATION MEASUREMENT OF DRILLING SHAFTS - Hassan, Essam E. (2020)
The inclination of drilling shafts from vertical axis poses some problems to workers in the oil exploration fields. A simple device is developed and tested at KFUPM to give the exact angle of the shaft axis off the vertical. Further, the design is capable of determining the direction of the shaft in the horizontal plane. The device is based on a laser beam source placed at the center of a hemisphere with light sensors distributed over its inner surface. The laser beam is held fixed in space through frictionless hinge and a pendulum attachment. As the shaft inclines an angle θ off the vertical, the hemisphere, being attached to the shaft, will have its axis making the same angle with the vertical and the laser beam will fall on a prescribed sensor indicating both the vertical and the horizontal angles of inclinations. The device is reliable since it has no moving parts, robust and quite accurate. Some results of a crude prototype are presented.